2021
DOI: 10.3390/pr10010037
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Vine Prunings by Slow Pyrolysis in a Fixed-Bed Reactor

Abstract: The paper aimed at studying the slow pyrolysis of vine pruning waste in a fixed bed reactor and characterizing the pyrolysis products. Pyrolysis experiments were conducted for 60 min, using CO2 as a carrier gas and oxidizing agent. The distribution of biochar and bio-oil was dependent on variations in heat flux (4244–5777 W/m2), CO2 superficial velocity (0.004–0.008 m/s), and mean size of vegetal material (0.007–0.011 m). Relationships among these factors and process performances in terms of yields of biochar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…The average TC content in grapevine pruning residues was 44.5%, which is similar to other studies [49][50][51], where authors reported values from 44.1% to 47.8%. In biochar, the average TC content was 75.4%, which agrees with the results of other studies (73.5%) [50], while a recent study reported even lower TC content (69.4%) [52]. Biochar TC content was not affected by rootstock type, showing a predominant effect of grapevine-pruning residues as feedstock [53].…”
Section: Discussionsupporting
confidence: 89%
“…The average TC content in grapevine pruning residues was 44.5%, which is similar to other studies [49][50][51], where authors reported values from 44.1% to 47.8%. In biochar, the average TC content was 75.4%, which agrees with the results of other studies (73.5%) [50], while a recent study reported even lower TC content (69.4%) [52]. Biochar TC content was not affected by rootstock type, showing a predominant effect of grapevine-pruning residues as feedstock [53].…”
Section: Discussionsupporting
confidence: 89%
“…Enhanced soil fertility not only reduces the need for additional fertilizer inputs but also boosts crop productivity, subsequently increasing CO 2 absorption; this, in turn, generates a range of advantages, encompassing agricultural, environmental, and economic benefits [30]. The impact of biochar on the soil-plant system is contingent on a multitude of variables, including the physicochemical attributes and quantity of biochar, the type and quantity of fertilizer, the specific plant species, soil properties, and prevailing climatic conditions [31]. The advantages of biochar amendment are particularly pronounced in sandy soils, with sandy loam soils following closely in terms of agronomic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant variables of alkaline pretreatment in terms of solid/liquid ratio (RSL = 0.5-1.5 g/100 mL), US amplitude (A = 20-60%), and working temperature (t = 30-50 °C) were selected as independent variables (factors).The effects of these process factors on dependent variables (responses), i.e., the yields of lignin (YL) and sugars (YS), were quantified using statistical models based on 2 3 factorial design [28]. According to a 2 3 factorial design, 8 experimental runs (1-8 in Table 1) were performed at 2 levels (minimum and maximum) of process factors.…”
Section: Statistical Modelsmentioning
confidence: 99%